Sosialisasi Dampak Penggunaan Gadget Pada Balita Pada PKK Kedulan, Kalasan, Yogyakarta - Suraya; Uminingsih (DHARMA BAKTI, 2021)
Information technology on gadget (cell phones) is more attractive because of many features offered it is,also getting smarter. Many manufacturers produce it at selling price and now it is easier to find in market, so that it can be reached by all levels of society up to the villages. The problem is that many current events are negative due to the use of gadgets, especially in toddlers. Therefore, the community needs insight into how to manage gadget wisely, especially if the gadget is provided for toddlers. The purpose of the activity is to provide information about the positive and negative impacts of using gadgets by toddlers if it is not followed by parental/caregiver assistance that guides the selection of content and the appropriate length of time for use for toddlers. The method of socialization carried out is by giving lectures and examples to PKK women and by doing the practice of using gadgets to them by explaining how to choose positive content, at the event of the regular monthly meetings in the village of Kedulan, Kalasan, Sleman.. At the end of the lecture the participants were asked to fill out a quiz about the material that has been delivered. The results of the socialization showed that most of them were understood the precentation material, but there were fill several questions asked direcly sothat the lecture immediately responded to the question and assisted with solutions.